PENERAPAN METODE MASTERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KRISTENDI KELAS V SDN 165728 TEBING TINGGI - Sarah Ginting (FIP Unimed, 2017)
This aim of this research is to improve learning result on christian educationthrough mastery learningmethod. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class V, SD Negeri165728 Tebing Tinggi which amounted to8 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the mastery learning method of mathematic subject can improve student learning result characterized by increased studentslearning output, namely the first cycle (75%), cycle II (100 %) and complete learn the clasical equal to 100%. Keywords: Mastery Learning, Christian Education